3(0)=-y+3

Simple and best practice solution for 3(0)=-y+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(0)=-y+3 equation:


3(0)=-y+3

We simplify the equation to the form, which is simple to understand
3(0)=-y+3

Reorder the terms in parentheses
+()=-y+3

Remove unnecessary parentheses
0=-y+3

We move all terms containing y to the left and all other terms to the right.
+1y=+3-0

We simplify left and right side of the equation.
+1y=+3

We divide both sides of the equation by 01 to get y.
y=3

See similar equations:

| 3-8h=35 | | 13-x=-8 | | 3(-2)=-y+3 | | 8x^2-46xy+11y^2=0 | | 30-3x=2+x | | 2m^2+13m+10=0 | | 2m^2-10-4=4 | | .5x+12=27 | | 16x-3y=18 | | 12x^2+133x+11=0 | | 350-167+v=2v | | 68+2x-30=x+42 | | Y+(-8)=-23 | | 24-x=42 | | 4x+5=2(3x+25) | | 6x-2=2x-10 | | (3x+8)(8x+7)=0 | | y=-0.50*40+121 | | y=-0.50*30+121 | | y=-0.50*20+121 | | 2x+48=322 | | 119=6x+17 | | 1500x=20x | | 1400+x=41900 | | 2x^2+4x-47=0 | | -16t^2+t+25=0 | | 2y^2+56=0 | | a+2b=-4 | | a+8b=8 | | 5x+1=-(x-7) | | 18-0.7(s-15)=0.8(9s-15) | | 16-x+36=47 |

Equations solver categories